Comparison of Relation between Attention Deficit Hyperactivity Disorder in Children with and without Simple Febrile Seizure Admitted in Arak Central Iran - SALEHI, Bahman; YOUSEFICHAIJAN, Parsa; SAFI ARIAN, Samira; EBRAHIMI, Somaieh; NAZIRI, Mahdyieh (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Salehi B, Yousefichaijan P, Safi Arian S, Ebrahimi S, Naziri M. Comparison of Relation between ADHD in Children with And without Simple Febrile Seizure Admitted in Arak Amir-Kabir Hospital on 2010-2011. Iran J Child Neurol. Autumn 2016; 10(3):56-61. Abstract Objective Febrile seizure is one of the most prevalent childhood convulsions with the most common age of onset at 14-18 mo old. Fever decreases the brain threshold for seizure. Attention Deficit Hyperactivity Disorder (ADHD) is also a neurologic-behavioral problem defined by attention deficit and hyperactivity according to DSM-IV criteria in which the child must have these signs in two different environments. There is controversy on the possible relation between febrile seizure and ADHD; while some studies approve a strong relation, some exclude any relation and some attribute ADHD to the side effects of other reasons. Materials & Methods This descriptive-analytic study enrolled all children of 3-12 yr old with febrile seizure (according to Nelson Pediatrics Textbook diagnosed by the pediatrician in charge) referring to Amir Kabir Hospital, Arak, central Iran in 2010-2011. Overall, 103 of them with no corporeal or psychological disorder (like depression, anxiety, schizophrenia and other CNS maternal disease) were compared to 103 children of the same age and gender admitted due to disease other than febrile seizure utilizing DSM IV criteria for ADHD. Data were analyzed using SPSS version 18. Results The hyperactivity disorder in the control and case group was 34.3% and 16.7%, respectively, denoted a significant relation between simple febrile seizure and hyperactivity. Conclusion Hyperactivity has a significant relation with febrile seizure in male gender, making further investigation in these children prudent for early diagnosis and management. References 1. Cunningham NR, Jensen P. ADHD. In: Kliegman RM, Stanton BF, Geme III JW, Schor NF, Behrman RE, eds. Nelson Textbook of pediatrics. 19th ed. Philadelphia: WB Saunders; 2011. p. 108-12. 2. Greenhill LL, Hechtman LI. Attention- Deficit Disorders. In: Sadock BJ, Sadock VA, Ruiz P, Kaplan HI, editors. Kaplan & Sadock’s Comprehensive Textbook of Psychiatry. 9th ed. Philadelphia: Wolters Kluwer Health/ Lippincott Williams & Wilkins; 2009.p.1223-1231. 3. Biederman J, Faraone SV, Keenak K, Steinjard R, Tsuang M. Familial association between ADHD and anxiety disorders. APA 1991; 48: 633–642. 4. Austin JK, Perkins SM, Johnson CS, Fastenau PS. Behavior problems in children at time of first recognized seizure and changes over the following years. Epilepsy Behave 2011;21(4):373-81. 5. Baum KT, Byars AW, deGrauw TJ, Dunn DW. The effect of temperament and neuropsychological functioning on behavior problems in children with new onset seizures. Epilepsy Behave 2010; 17(4):467-73. 6. Fastenau PS, Johnson CS, Perkins SM, Byars AW. Neuropsychological status at seizure onset in children: risk factors for early cognitive deficits. Neurology 2009;73(7):526-34 7. Anna W, Kelly B, Cynthia S, Ton J. The relationship between sleep problems and neuropsychological functioning in children with first recognized seizures Epilepsy Behave 2008; 13(4):607-13. 8. Ying C, Nai W, Chao C, Shan T, Jing J. Neurocognitive Attention and Behavior Outcome of School-Age Children with a History of Febrile Convulsions: A Population Study. Epilepsies 2000; 41(4):412-20. 9. Chang YC, Guo NW, Wang ST, Huang CC. Working memory of school- aged children with a history of febrile convulsions: a population study. Neurology 2001; 57(1):37-42. 10. Hesdorffer DC, Ludvigsson P, Olafsson E, Gudmundsson G. ADHD as a Risk Factor for Incident Unprovoked Seizures and Epilepsy in Children. Arch Gen Psychiat 2004; 61(7):731-6. 11. Dunn D, Harezlak J, Ambrosius W, Austin J. Teacher assessment of behavior in children with new – onset seizures. Seizure 2002; 11(3):169-75. 12. Tsai JJ, Wang ST. Assessing the behavioral and cognitive effects of seizures on the developing brain. Prog Brain Res 2002; 135: 377-90. 13. Austin J, Harezlak J, Dunn D, Huster G. Behavior Problems in children before first recognized seizures. Pediatrics 2001; 115-122. 14. Yousefichaijan P, Eghbali A, Rafiei M, Sharafkhah M, Zol M, Firouzifar M. The Relationship between iron deficiency anemia and simple febrile convulsion in children. J Pediatr Neurosci 2014; 9: 110-114. 15. Yousefichaijan P, Salehi B, Firouzifar M, Sheikholslami H. The correlation between ADHD and enuresis in children with nocturnal enuresis. I.U.M.S, 2nd week, 2012. 184(30): 8-14.